Temporal changes on the effect of rock fragments in interrill soil loss: a simulation experiment and a simple descriptive model - Figueiredo, Tomás de (2011)
Soils with rock fragments have been studied under several aspects in the last years. Research shows that a single pattern in the erosional response of these soils to rainfalls is not always found. In order to contribute to the understanding of this topic, an experiment was carried out, simulating interrill areas covered by rock fragments. This paper specifically aims at presenting and discussing temporal changes on sediment exported from such areas, also introducing a simple descriptive model to represent soil loss temporal evolution. Small bottom perforated boxes, 612 cm2 area, were filled with a silt-loam fine earth, very poor in organic matter, covered with simulated rock fragments and leaned at 10% slope gradient. The experiment comprised the exposure to 240 mm natural rainfall of 48 boxes corresponding to selected combinations, 4 replicates each, of rock fragments cover (0, 17, 30 and 66%), size (2, 4 and 10 cm), form (rectangular and circular) and position (resting on top and embedded). During the experiment boxes were kept under near saturation soil water conditions. Water and soil exported from the boxes as infiltration, runoff, wash and splash were measured after each period of precipitation. Recorded values of soil loss plotted against precipitation, both expressed in cumulative terms, follow a sigmoid curve. This pattern of response was interpreted as a result of crust formation on soil surface exposed to rainfalls, a hypothesis suggested by observations during the experiment and confirmed at its end. Parameters of this model were related with rock cover and characteristics. The effect of rock fragments on soil loss varies with time, a conclusion that must be taken into account when interpreting either results from experiments with different durations or the evolution of stoniness on eroding surfaces. Os solos pedregosos vêm sendo estudados sob diversos aspectos nos últimos anos. No que respeita à perda de solo, os resultados publicados mostram todavia a dificuldade em estabelecer um padrão único de resposta destes solos às precipitações erosivas. Com vista a aprofundar conhecimentos sobre este tópico, foi instalado um ensaio experimental, simulando superfícies com variável pedregosidade sujeitas a erosão interssulcos. Constitui objectivo deste trabalho apresentar e discutir a evolução temporal da perda de solo nessas superfícies, propondo a sua representação num modelo descritivo simples. O ensaio compreendeu a exposição a 240 mm de chuva natural de um conjunto de tabuleiros com 612 cm 2 de área e 10% de declive, contendo terra fina franco-limosa, muito pobre em matéria orgânica, coberta por elementos grosseiros simulados. Os tabuleiros mantiveram-se próximo da saturação de água. Para além do solo nu, testaram-se tratamentos com 4 repetições cada, correspondendo a combinações específicas de 3 fracções de cobertura (17, 30 e 66%), 3 dimensões (2, 4 e 10 cm), 2 formas (rectangulares e circulares) e 3 posições (pousados à superfície, semi-aflorantes e aflorantes). A infiltração e o escoamento, e as perdas de solo neste e por salpico, foram medidas ao longo do ensaio, na sequência de períodos de precipitação. A perda de solo acumulada representada em função da precipitação acumulada ao longo do ensaio segue uma curva sigmóide. Este modelo de resposta foi interpretado como resultando da formação da crosta superficial do solo exposto, hipótese sugerida pela observação no decorrer do ensaio e confirmada no final. Os parâmetros da curva sigmóide correlacionaram-se com a fracção de cobertura, tendo sido também explorada a relação com outros parâmetros descritivos da pedregosidade. A conclusão de que a relação entre perda de solo e pedregosidade é temporalmente variável, traz consequências para a interpretação quer de resultados de ensaios com diferente duração, quer da evolução temporal da pedregosidade em superfícies erodidas.